An Investigation to Assess Occlusal and Psychological Parameters in Bruxism - Nasir, Umar; Ahmad, Haseeb; Fatima Tariq, Sahibzadi; Mahwishzeb; Shafiq, Fiza; Qureshi, Asfandyar (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the anxiety and occlusal features in bruxism by means of T-Scan III and Hospital Anxiety and Depression Scale correspondingly. Study design: Case control study Place and duration of study: Department of Oral Medicine, Khyber Medical University-Institute of Dental Sciences, Kohat from 1st December 2020 to 30th November 2021. Methodology: This study comprised of a cluster of fifty patients with bruxism (Cluster Bxm) and fifty healthy persons as control cluster (Cluster NBxm). Patients were nominated from outdoor patients coming to Private Dental Teaching Hospital in Peshawar with the principal grievance of sensitivity of the teeth due to routine crushing. For the selection of cases, American Academy of Sleep Medicine (AASM) was followed. Supplementary grounded on assessment of era and sex, controls were nominated. Hospital Anxiety and Depression Scale (HADS) survey was asked equally from the clusters to assess the depression and anxiety. Record of occlusal strictures in both the clusters was completed numerically by using T-Scan III. Results: Cluster Bxm had expressively superior mean tooth wear index (20.35±9.7) than cluster NBxm (10.20±7.29). Cluster Bxm had ominously advanced anxiety (13.33±3.97/9.17±1.92) and depression scores (9±1.83/7.17±2.34) as equated to NBxm. The disclusion period of cluster Bxm was 0.953±0.860 and that of cluster NBxm was 0.358±0.390 (p=0.009). Conclusions: Patients with advanced stage of depression, anxiety and amplified disclusion period may have more fondness to misery from bruxism (p<0.05).